Analysis of Bankruptcy Prediction at PT. Indofarma Tbk uses the Altman Z-Score Method for the 2021-2023 Period: Analisis Prediksi Kebangkrutan pada PT. Indofarma Tbk menggunakan Metode Altman Z-Score Periode 2021-2023 - Moh. Rasyid; Martha Martha; Edi Yanto; Rendy Aziz Syahputra; Masri Arfandi (STIE MUJAHIDIN TOLITOLI, 2026)
This research aims to find out the potential for bankruptcy in PT. Indofarma Tbk uses the Altman Z-Score method for the 2021-2023 period. The type of research used is quantitative descriptive. The secondary data source is in the form of financial statements of PT. Indofarma Tbk for the 2021-2023 period accessed through the www.idx.co.id website The data analysis method used used was using the Modified Altman Z-Score method which used four variables, namely: Working capital/total assets (X1), retained earnings/total assets (X2), Earnings before interest and taxes/total assets (X3), net book equity/total book value (X4). Based on the results of the analysis and discussion, it was concluded that by using the Altman Z-Score method PT. Indofarma Tbk for the 2021-2023 period is classified as a company that is predicted to experience bankruptcy. This is characterized by a Z-Score result below 1.1, meaning a critical financial condition. The significant decline in various financial ratios, including liquidity and profitability, reflects the ever-increasing accumulation of losses and increasingly pronounced bankruptcy ratios.